Zastosowanie technologii reflektometrii w dziedzinie czasu do badań parametrów gruntów = Application of time do main reflectometry technology for monitoring soil parameters - Rybski, Ryszard; Frygiel, Tomasz; Kostecki, Jakub; Piotrowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The paper presents a concept of constructing a testing station based on Time Domain Reflectometry (TDR) method, which enables non-destructive testing of ground sample moisture content at many levels of its vertical cross-section with the functionality of automatic registration of measurement series results.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne